Efektivitas Konseling Kelompok untuk Meningkatkan Keterampilan Sosial Siswa - Rizki Hamdan Saputra Nasution; Ihsan Hasibuan; Ali Akbar; Ranti Daulay; Ika Daulay (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study was motivated by the importance of students’ social skills in supporting successful interactions in educational settings, which are currently on the decline due to technological advancements and increasingly individualistic interaction patterns. The purpose of this study was to determine the effectiveness of group counseling in improving students’ social skills. The method used was a quantitative approach employing a pretest-posttest experimental design with a control group. The study sample consisted of 30 students divided into two groups the experimental group and the control group using purposive sampling. The research instrument was a social skills scale that had been validated for both validity and reliability, while data analysis employed a paired t-test. The results showed a significant improvement in the social skills of students in the experimental group with a significance level of p = 0.000 (p < 0.05) and an average increase of 21.67 points, while the control group showed no significant change. The conclusion of this study is that group counseling is effective in improving students’ social skills and can therefore be recommended as a guidance and counseling service strategy in schools.